Networked control system – an overview - Asif, Seemal; Webb, Philip (Foundation of Computer Science, 2015)
Networked Control System (NCS) is fetching researchers’ interest from many decades. It’s been used in industry which range from manufacturing, automobile, aviation, aerospace to military. This paper gives the general architecture of NCS and its fundamental routes. It also touches to its advantages and disadvantages and some of the popular controller which include PID (Proportional-Integral-Derivative) and MPC (Model Predictive Control).
Keywords: NCS; Networked Control System; PID; MPC